(untitled) (Current Horticulture, 2024)
Potassium (K) nutrition is very important for high yield and quality of litchi (Litchi chinensis Sonn.) fruits. However, overdose of fertilizer K, especially when the application ratio of fertilizer N:K2O is <1:1, can induce fruit cracking in litchi by reducing Ca concentrations in all parts of the fruit. Common abbreviations and notes: K = potassium; N = nitrogen; Ca = calcium; B = boron; Mg = magnesium; OT = ordinary (litchi) trees; KT = litchi trees that received excess potassium chloride (KCl).